2008
DOI: 10.1186/1471-2407-8-46
|View full text |Cite
|
Sign up to set email alerts
|

Cervical squamous carcinoma cells are resistant to the combined action of tumor necrosis factor-α and histamine whereas normal keratinocytes undergo cytolysis

Abstract: Background: Previous reports showed that mast cells can typically be found in the peritumoral stroma of cervix carcinomas as well as in many other cancers. Both histamine and TNF-α are potent preformed mast cell mediators and they can act simultaneously after release from mast cells. Thus, the effect of TNF-α and histamine on cervical carcinoma cell lines was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Interestingly, the authors found that the combination of 10 µM histamine and 1 ng ml -1 TGF-β resulted in an additive effect on MMP-9/TIMP-1 production. This result thus further extends the previous findings about histamine-TNF-α and histamine-IFN-γ combinations in keratinocyte stimulation (Matsubara et al, 2005;Giustizieri et al, 2004;Diaconu et al, 2008). In the ex vivo experiments in skin biopsies, the authors demonstrated further that exogenously added 10 µM histamine induced MMP-9 in skin biopsies after incubation for 16 h, as detected with zymography of the extracted protein.…”
Section: Histamine Induces Mmp-9 In Keratinocytes and Epidermissupporting
confidence: 86%
See 1 more Smart Citation
“…Interestingly, the authors found that the combination of 10 µM histamine and 1 ng ml -1 TGF-β resulted in an additive effect on MMP-9/TIMP-1 production. This result thus further extends the previous findings about histamine-TNF-α and histamine-IFN-γ combinations in keratinocyte stimulation (Matsubara et al, 2005;Giustizieri et al, 2004;Diaconu et al, 2008). In the ex vivo experiments in skin biopsies, the authors demonstrated further that exogenously added 10 µM histamine induced MMP-9 in skin biopsies after incubation for 16 h, as detected with zymography of the extracted protein.…”
Section: Histamine Induces Mmp-9 In Keratinocytes and Epidermissupporting
confidence: 86%
“…Furthermore, histamine can augment, through the H1 receptor, IFN-γ-induced expression of major histocompatibility complex class I, ICAM-1, GM-CSF, CCL-5/RANTES, CCL-2/MCP-1, CCL-20/MIP-3α, and CXCL-10/IP-10 in human keratinocytes (Giustizieri et al, 2004). On the other hand, histamine has been thought to control the growth of the epidermis, because histamine can inhibit the growth of monolayer keratinocytes and keratinocyte epithelium, and this effect is potentiated even to cytolysis when histamine affects keratinocytes together with TNF-α (Diaconu et al, 2008).…”
Section: Histamine and Epidermismentioning
confidence: 99%
“…Although a moderate TNF level is necessary to maintain cell protected and prevent certain diseases through regulation of the immune response, excessive TNF secretion due to pathological conditions is associated with autoimmune diseases, infectious diseases and malignant tumors (9). In cervical cancer, TNF promotes cell cycle progression by increasing cyclin-dependent kinase activity and HPV16 E6/E7 RNA expression in HPV-immortalized keratinocytes (9, 10). It also enhances the transcription and stability of epidermal growth factor receptor (EGFR), resulting in cell proliferation and tumorigenesis (9, 11).…”
Section: Introductionmentioning
confidence: 99%